Using Wattpad Platform To Improve Writing Skill Of The Tenth-Grade Students of SMA Negeri 2 Palu - Syahwalya, Fitra; Manurung, Konder; Patmasari, Andi; Mukrim, Mukrim (Journal of Learning Improvement and Lesson Study, 2024)
The aim of this research aims to prove if the use of the Wattpad platform can improve the writing skills of the tenth-grade students of SMA Negeri 2 Palu. The research method is a quantitative method with a quasi-experimental design. To collect data, this study used pre-test and post-test. The subjects of this study were divided into two, the experimental group and the control group. The research instrument is a writing test with narrative text type.The results showed that the post-test t-counted value (6.608) was greater than the t table (1.670) by applying a significance level of 0.05 with degrees of freedom (df) = 64. Based on the results of the study, if the t value is greater than the t table, then H0 is rejected and Ha is accepted,.In other words, the effect of using Wattpad platform on students' writing skills has a significant effect.